Online Public Responses to the "Send Her Back" Chant at the 2019 Greenville Rally. Issue 4 (4th July 2021) - Bresnahan, Mary; Roscizewski, Alexa; Whitaker, Sarah; Cossmann, Hannah
ABSTRACT: The Squad is a group of four progressive women of colour elected to the U.S. Congress in 2018 who have been vocal critics especially of immigration and environmental policies. During a Republican rally in North Carolina in 2019, Trump disparaged the Squad for being critical of him. The crowd responded chanting "Send her/them back." This study conducted a content analysis of public comments posted on four online news sites assessing rejection or approval for this chant. Content analysis showed a striking difference across the sites based on the amount of approval for the chant. Comments on Fox News and a conservative Twitter site supported the chant and characterized members of the Squad as obstructionist and uncooperative. There was little support for the chant on the Washington Post and the New York Times sites. This study examined how users who posted these comments explained/justified their responses to the chant.